2018
DOI: 10.1111/bjhp.12350
|View full text |Cite
|
Sign up to set email alerts
|

The centrality of health behaviours: A network analytic approach

Abstract: Objectives. Since behavioural risk factors are the foremost causes of disability and premature mortality, developing new perspectives for understanding them is of utmost importance. This paper describes an innovative approach that conceptualizes healthrelated behaviours as nodes in a weighted network. Design & Methods.Using self-reported data from a representative sample (n = 374), a network of 37 health behaviours was analysed, with the aim of identifying 'central' nodes, that is, behaviours that are likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 99 publications
(158 reference statements)
2
17
0
Order By: Relevance
“…To the best of our knowledge, this is the first empirical evidence of cross-behavioural effects between healthy lifestyle behaviours and situationally unique behaviours demanded as a protection from a pandemic. The findings are consistent with prior reports on cross-behaviour associations [10,13], and support the importance of considering the interconnectedness among healthrelated behaviours [11]. Several explanations have been offered to account for cross-behaviour effects, some even leading to contradictory predictions.…”
Section: Healthy Lifestyle Behaviours As Predictors Of Coronavirus Prsupporting
confidence: 90%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first empirical evidence of cross-behavioural effects between healthy lifestyle behaviours and situationally unique behaviours demanded as a protection from a pandemic. The findings are consistent with prior reports on cross-behaviour associations [10,13], and support the importance of considering the interconnectedness among healthrelated behaviours [11]. Several explanations have been offered to account for cross-behaviour effects, some even leading to contradictory predictions.…”
Section: Healthy Lifestyle Behaviours As Predictors Of Coronavirus Prsupporting
confidence: 90%
“…However, the coronavirus pandemicis new and most people have had no prior experience with such an occurrence. Nevertheless, there might be a relationship between the new recommendedcoronavirus-related protective behaviours and healthy lifestyle behaviours.Indeed, numerous studies have suggested that engaging in one health behaviourmight result in a higher likelihood of engaging in other health behaviours [10][11][12][13][14][15]. For example, smoking was found topredict alcohol consumption [16], and engaging in physical activity was found to promote healthy nutritional habits [17].…”
Section: Predicting Current Health Behaviours From Past Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…Much health behaviour is interrelated. Involvement in one health behaviour can affect engagement in other behaviour (Nudelman, Kalish, & Shiloh, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another emerging area of theorising in health psychology involves developing theory to account for multiple behaviours (Albarracín et al, 2018;Conner et al, 2016;Fleig et al, 2015;Nudelman et al, 2018). These developments readily generalise to implementation science, where healthcare professionals perform multiple behaviours competing for limited time (Jaén et al, 1994;Presseau et al, 2009).…”
Section: Recommendationmentioning
confidence: 99%